Putting Environmental Injustice on the Map: Ecotestimonies from the Global South - Erin S Finzer (Studies in 20th & 21st Century Literature, 2015)
This introductory essay to STTCL 39.2 discusses the importance of testimony as a flexible literary genre that can tell the stories of environmental injustice in the Global South, which is disproportionately affected by environmental violence and less represented in the growing global environmental movement.
Keywords: ecotestimony; environmental injustice; Global South; testimonio; resistance literature; climate change